2019
DOI: 10.3791/59051
|View full text |Cite
|
Sign up to set email alerts
|

Handling and Assessment of Human Primary Prostate Organoid Culture

Abstract: This paper describes a detailed protocol for three-dimensional (3D) culturing, handling, and evaluation of human primary prostate organoids. The process involves seeding of epithelial cells sparsely in a 3D matrix gel on a 96-well microplate with media changes to cultivate expansion into organoids. Morphology is then assessed by whole-well capturing of z-stack images. Compression of z-stacks creates a single in-focus image from which organoids are measured to quantify a variety of outputs, including circularit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…After gently washing with 1X PBS 3 times, organoids were fixed with 4% paraformaldehyde (Electron Microscopy Sciences, Hatfield, PA, USA) for 30 min at room temperature (RT), and washed and stored in PBS until immunostaining. Immunofluorescent staining used modifications of previous methods [ 25 , 26 , 27 , 28 ]. Briefly, to reduce auto-fluorescence, 250 µL of 50 mM NH 4 Cl in 1X PBS were added into each well of the slides at RT for 30 min while gently shaking.…”
Section: Methodsmentioning
confidence: 99%
“…After gently washing with 1X PBS 3 times, organoids were fixed with 4% paraformaldehyde (Electron Microscopy Sciences, Hatfield, PA, USA) for 30 min at room temperature (RT), and washed and stored in PBS until immunostaining. Immunofluorescent staining used modifications of previous methods [ 25 , 26 , 27 , 28 ]. Briefly, to reduce auto-fluorescence, 250 µL of 50 mM NH 4 Cl in 1X PBS were added into each well of the slides at RT for 30 min while gently shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Organoids were grown as previously described by our group (McCray et al, 2019b;Richards et al, 2019). Briefly, epithelial cells were thawed and grown to passage 2 on collagen-coated dishes to ~70% confluency.…”
Section: Organoid Culturementioning
confidence: 99%
“…Briefly, epithelial cells were thawed and grown to passage 2 on collagen-coated dishes to ~70% confluency. Epithelial cells were plated singly and sparsely (100-1,000 cells per well, depending on patient-specific growth ability) in 100 μL of 10%-50% growth factor-reduced Images of organoid cultures were acquired and analyzed as previously described by our group (McCray et al, 2019b;Richards et al, 2019). Briefly, images were captured at 4x magnification using the Evos FL Auto 2 Imaging System (Thermo Fisher Scientific, MA), and up to 50 z-planes were captured per quadrant of a 96-well plate.…”
Section: Organoid Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Tumor microenvironments are heterogenous and consist of different cell types such as endothelial cells, stromal cells, and immune cells. Studies have shown that stromal cells in the tumor microenvironment (TME) help promote PCa progression and spread [ 19 , 20 ]. One of the main components of the TME are fibroblasts, specifically cancer-associated fibroblasts (CAFs).…”
Section: Introductionmentioning
confidence: 99%